'Decision support system (DSS) for prevention of cardiovascular disease (CVD) among hypertensive (HTN) patients in Andhra Pradesh, India' - a cluster randomised community intervention trial - Anchala Raghupathy; Pant Hira; Prabhakaran Dorairaj; Franco Oscar H (BMC, 2012)
Abstract Background Very few studies having decision support systems as an intervention report on patient outcomes for cardiovascular disease in the Western world. The potential role of decision support system for the management of blood pressure among Indian hypertensives remains unclear. We propose a cluster randomised trial that aims to test the effectiveness and cost effectiveness of DSS among Indian hypertensive patients. Methods The trial design is a cluster randomised community intervention trial, in which the participants would be adult male and female hypertensive patients, in the age group of 35 to 64 years, reporting to the Primary Health Care centres of Mahabubnagar district, Andhra Pradesh, India. The objective of the study is to test the effectiveness and compare the cost effectiveness and cost utility among hypertensive subjects randomized to receive either decision support system or a chart based algorithmic support system in urban and rural areas of a district in the state of Andhra Pradesh, India (baseline versus 12 months follow up). The primary outcome would be a comparison of the systolic blood pressure at 0 and 12 months among hypertensive patients randomized to receive the decision support system or the chart based algorithmic support system. Computer generated randomisation and an investigator and analyser blinded method would be followed. 1600 participants; 800 to each arm; each arm having eight clusters of hundred participants each have been recruited between 01 August 2011 - 01 March 2012. A twelve month follow up will be completed by March 2013 and results are expected by April 2013. Discussion This cluster randomized community intervention trial on DSS will enable policy makers to find out the effectiveness, cost effectiveness and cost utility of decision support system for management of blood pressure among hypertensive patients in India. Most of the previous studies on decision support system have focused on physician performance, adherence and on preventive care reminders. The uniqueness of the proposed study lies in finding out the effectiveness of a decision support system on patient related outcomes. Trial registration CTRI/2012/03/002476, Clinical Trial Registry - India.